The Prevalence and Burden of Migraine and Severe Headache in the United States: Updated Statistics From Government Health Surveillance Studies. Issue 1 (January 2015) - Burch, Rebecca C.; Loder, Stephen; Loder, Elizabeth; Smitherman, Todd A.
<x xml:space="preserve">Abstract</x> Background and Objectives The US National Center for Health Statistics, which is part of the Centers for Disease Control, conducts ongoing public health surveillance activities. The US Armed Forces also maintains a comprehensive database of medical information. We aimed to identify the most current prevalence estimates of migraine and severe headache in the United States adult civilian and active duty service populations from these national government surveys, to assess stability of prevalence estimates over time, and to identify additional information pertinent to the burden and treatment of migraine and other severe headache conditions. Methods We searched for the most current publicly available summary statistics from the National Ambulatory Medical Care Survey, the National Hospital Ambulatory Medical Care Survey, and the National Health Interview Survey (NHIS). Summary data from the Defense Medical Surveillance System were also obtained, and PubMed was also searched for publications reporting summary statistics based on these studies. Data were abstracted, double‐checked for accuracy, and summarized over time periods and as a function of demographic variables. Results 14.2% of US adults 18 or older reported having migraine or severe headache in the previous 3 months in the 2012 NHIS. The overall age‐adjusted 3‐month prevalence of migraine in females was 19.1% and in males 9.0%, but varied substantially depending on age. The prevalence of migraine was highest in females 18‐44, where the 3‐month prevalence of migraine or severe headache was 23.5%. The 3‐month prevalence of migraine or severe headache has remained relatively stable over the period of 2005‐2012, with an average prevalence of 20.2% in females, 9.4% in males, and 20.2% overall. During this time, the average female to male sex ratio for migraine or severe headache was 2.17. The unadjusted 1‐year prevalence of migraine in active duty US military service members varied from 1% to 1.9% between 1998 and 2010, ranging from 0.7% to 1.2% in males and 3.5% to 6% in females. The 1‐year prevalence of "other headache" in this military population ranged from a low of 1.9% in 2003 to a high of 3% in 2010. Headache or pain in the head was the fourth leading cause of visits to the emergency department (ED) in 2009‐2010, accounting for 3.1% of all ED visits. Across all ambulatory care settings, migraine accounted for 0.5% of all visits and other headache presentations for 0.4% of all ambulatory care visits. 52.8% of all visits for migraine occurred in primary care settings, 23.2% in specialty outpatient settings, and 16.7% in EDs. In 2010, opioids were administered at 35% of ED visits for headache, while triptans were administered in only 1.5% of visits. Conclusions This report summarizes the most recent government statistics on the prevalence and burden of migraine and severe headache in the US civilian and active duty military populations. The prevalence of migraine headaches is high, affecting roughly 1 out of every 7 Americans annually, and has remained relatively stable over the last 8 years. Migraine and headache are leading causes of outpatient and ED visits and remain an important public health problem, particularly among women during their reproductive years.